Clinical Profile of Acute Gastroenteritis in Children at a Tertiary Centre - Jha, Anand Kumar; Shah, Sweta; Das, Bikash; Das, Subash Kumar (Med Phoenix, 2023)
Introduction: Acute gastroenteritis accounts for millions of deaths each year in young children, mostly in developing communities. diarrhoea, vomiting and fever are the most common presenting symptoms. The aim of the study was to describe the clinical profile of Acute Gastroenteritis in children at National Medical College and Teaching Hospital, Birgunj Materials and Methods: This descriptive cross-sectional study was carried out in pediatric ward and Intensive Care Unit at National Medical College and Teaching Hospital, Birgunj, Nepal for 6 months (November 2021 to April 2021). Ethical clearance and informed written consent were taken for the study. Results: Among 138 cases enrolled in the study, most common symptoms were diarrhoea, vomiting and fever. Signs of some dehydration was seen in 39.1% of the cases whereas 4.4% cases had signs of severe dehydration. Oral rehydration Solution (ORS) was mainstay of treatment along with zinc and probiotics. Antibiotics was used in 52.2% cases. Among all the cases, 75.4% cases and their caretakers did not routinely wash their hands. Conclusions: Diarrhoea, vomiting and fever are the most common symptoms in acute gastroenteritis. Use of ORS and zinc is recommended for the management in acute gastroenteritis in children. Antibiotic therapy should be used judiciously in the management of acute gastroenteritis. Increase awareness among the public about proper hand washing and hygiene can significantly reduce the incidence of diarrhoea and other infectious diseases in children.